Trophic transfer, bioaccumulation, and potential health risk of trace elements in water and aquatic organisms of Yundang Lagoon at Xiamen in China. (2nd January 2023) - Uddin, Mohammad Mazbah; Peng, Guogan; Huang, Lingfeng
Abstract: In this study, distribution and accumulation of trace elements (Cr, Mn, Ni, Cu, Zn, As, Cd, and Pb) in water, tissues of aquatic organisms (e.g. fishes: Oreochromis niloticus, Platycephalus indicus, Clupanodon punctatus ; crabs: Charybdis japonica, Portunus sanguinolentus, and Charybdis varuegata ; prawns: Litopenaeus vannamei, Metapenaeus joyneri, Penaeus japonicas, Penaeus penicillatus ; mollusks: Mytilus spp., Perna spp.), and trophic transfer in food web were investigated in Yundang Lagoon at Xiamen in China. Most of the studied metals such as Cr, Mn, Ni, Cu, Cd, and Pb were biodiluted in the food web except As which was biomagnified in the food web. Moreover, the target hazard quotient and total target hazard quotient risk values were higher than threshold limit values indicating that non-carcinogenic health risk to the inhabitants due to consumption of aquatic organisms.